Sex-specific lifespan and its evolution in nematodes - Ancell, Henry; Pires-daSilva, Andre (Seminars in cell & developmental biology, 2017)
•Nematode diversity offers great potential for understanding sex-specific aging.•Sexual dimorphism of lifespan is plastic and context-dependent.•Nematode studies highlight the importance of sex-specific selection.•Costs related to natural conditions must be incorporated into experimental design. Differences between sexes of the same species in lifespan and aging rate are widespread. While the proximal and evolutionary causes of aging are well researched, the factors that contribute to sex differences in these traits have been less studied. The striking diversity of nematodes provides ample opportunity to study variation in sex-specific lifespan patterns associated with shifts in life history and mating strategy. Although the plasticity of these sex differences will make it challenging to generalize from invertebrate to vertebrate systems, studies in nematodes have enabled empirical evaluation of predictions regarding the evolution of lifespan. These studies have highlighted how natural and sexual selection can generate divergent patterns of lifespan if the sexes are subject to different rates or sources of mortality, or if trade-offs between complex traits and longevity are resolved differently in each sex. Here, we integrate evidence derived mainly from nematodes that addresses the molecular and evolutionary basis of sex-specific aging and lifespan. Ultimately, we hope to generate a clearer picture of current knowledge in this area, and also highlight the limitations of our understanding.